Pengaruh Kompetensi dan Profesionalisme Dosen Akuntansi Terhadap Tingkat Pemahaman Mahasiswa Akuntansi: The Effect of Competence and Professionalism of Accounting Lecturers on the Level of Understanding of Accounting Students - Mulyadi, Ahmad (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study is to determine the influence of competence and professionalism of accounting lecturers to the level of understanding of accounting students. The object of this research is accounting student of 8th semester at Muhammadiyah University of . Data collection in this study using questionnaires that are given to students of the faculty of economics and business at the University of . Sampling using technique that sampling using . Data analysis using linear regression and data processing with SPSS 23. The results of this study indicate the competence of lecturers influence the level of understanding of accounting. Professionalism of lecturers influences the level of understanding of accounting. Competence and professionalism of accounting lecturers influence the level of understanding of accounting students in the faculty of economics and business of Muhammadiyah University of Sidoarjo